Identifikasi Akuifer dan Estimasi Volume Air Tanah di Kecamatan Tempilang, Kabupaten Bangka Barat, Kepulauan Bangka Belitung, untuk Mendukung Kebutuhan Air Tanah pada Perkebunan Kelapa Sawit Menggunakan Metode Geolistrik - Shan Muhammad Akhtar; lan Darma Syahputra; Risky Martin Antosia; Acep Ruchimat (Mataram University, 2026)
This study aims to identify aquifer characteristics and estimate groundwater volume in Tempilang District, West Bangka Regency, to support water demand resulting from oil palm plantation activities. The method applied was the geoelectrical Vertical Electrical Sounding (VES) using the Schlumberger configuration at ten measurement points, consisting of six points within the Alluvium Formation (Qa) and four points within the Tanjung Genting Formation (TRt). Apparent resistivity data were processed using least-square inversion with IPI2WIN software to obtain true resistivity values, which were subsequently interpreted through correlation with borehole data and previous studies. The results indicate that the main aquifer within the Alluvium Formation is developed in sand layers with varying thicknesses, approximately 32 m in the southern zone, 21 m in the central zone, and 36 m in the northern zone, with an average thickness of 27.5 m. Based on the Alluvium Formation area of 7,884 ha, the aquifer volume is estimated to reach 2.145 × 10⁹ m³. Assuming an effective porosity of 15%, the theoretical exploitable groundwater volume is approximately 3.21 × 10⁸ m³. This estimation suggests that the groundwater potential in Tempilang District is theoretically sufficient to meet the water demand of oil palm plantations; however, its utilization requires sustainable management.